Cultivar substitution as a remediation strategy in radiocaesium and radiostrontium contaminated areas - Penrose, Beth (2016)
Radioisotopes of caesium (Cs) and strontium (Sr) have been distributed in the environment due to weapons testing, nuclear power production and accidents at nuclear facilities. Radiocaesium and radiostrontium are of major concern in the medium to long term following accidental releases as they have high energies, long half lives (137Cs≈30 years; 90Sr≈29 years) and their easy assimilation into biological systems due to their similarity to the biologically important elements potassium (K) and calcium (Ca), respectively. Radio-caesium and -strontium are transferred to humans primarily via plant root uptake, and therefore minimising this uptake has been the focus of a number of remediation strategies, such as ploughing and fertiliser application. Species or cultivar substitution, where a species/cultivar that has higher uptake is replaced by a species/cultivar that has lower uptake, has been proposed as an effective and socially acceptable remediation strategy for contaminated agricultural land, but not enough is known about its efficacy for it to be recommended internationally. The aim of this thesis is to evaluate the potential of species or cultivar substitution as a remediation strategy for contaminated agricultural areas. Chapter 2 consists of meta-analysis of the available data (115 experiments) on the inter-cultivar variation in Cs and Sr accumulation by 27 plant species. Chapter 3 includes experiments conducted in the laboratory (UK) and two experiments in the field (Ukraine) investigating inter-cultivar variation in radiocaesium and radiostrontium accumulation in Brassica oleracea, and whether consistently lower-accumulating cultivars could be identified. Chapter 4 details analysis of samples from grass breeding experiments in Aberystwyth and Edinburgh (UK) from four forage grass species; hybrid ryegrass (Lolium perenne L. x Lolium multiflorum Lam.), L. perenne, L.multiflorum and Festuca arundinacea Shreb., and investigates inter-species and inter-cultivar variation in uptake of stable Cs and Sr. Hybrid ryegrass cultivars that were lower-accumulating in Cs and/or Sr were also identified. Chapter 5 compares the stable Cs and Sr uptake in six L. perenne and two F. arundinacea cultivars grown in Aberystwyth and Narodychi (Ukraine). Chapter 6 compares the performance in terms of yield and forage quality (elemental concentrations, digestibility and water soluble carbohydrate content) of six hybrid ryegrass cultivars and ten F. arundinacea cultivars identified as consistently lower-accumulating in Cs and/or Sr against the performance of two commercial hybrid ryegrass cultivars. The mean inter-cultivar variation in Cs and Sr was 1.8-fold and 2.0-fold,respectively when 27 plant species were studied. Thirty-five-fold variation in radiocaesium and 23-fold variation in radiostrontium was found between c.70 Brassica oleracea cultivars. In two field experiments in Ukraine, five cultivars had consistently lower radiocaesium concentration ratios and two cultivars consistently lower radiostrontium concentration ratios. One cultivar had lower radiocaesium and radiostrontium concentration ratios. Festuca arundinacea cultivars had lower Cs and Sr concentration ratios than cultivars of hybrid ryegrass, L. perenne and L. multiflorum. Three out of 17 hybrid ryegrass cultivars had consistently lower Cs concentration ratios, two cultivars consistently lower Sr and one consistently lower Cs and Sr. Despite differences in soil properties and environmental conditions, F. arundinacea cultivars grown in Aberystwyth and Narodychi accumulated less stable and radioactive Cs and Sr than L. perenne cultivars. One L. perenne cultivar also accumulated less Cs and Sr at both sites. F. arundinacea cultivars accumulated less Cs and Sr than commercial hybrid ryegrass cultivars, but alsohad up to 59% lower yield and a reduction of up to 19% in K accumulation, up to 46% in Ca accumulation, up to 7% in dry matter digestibility and up to 17% in water soluble carbohydrate content. Selecting lower accumulating cultivars was found to reduce Cs and Sr accumulation less, but with a smaller yield penalty and a smaller reduction in digestibility and water soluble carbohydrate content. It is concluded that species and cultivar substitution could be an effective remediation strategy in contaminated agricultural land provided implications for yield and quality are considered.